Balance Brings Beauty - Fischer, J.; Horcea-Milcu, A. I.; Lang, D. J.; Thale-Bombien, L.; Abson, D. J.; Apetrei, C. I.; Clarke, E.; Derwort, P.; Dorninger, C.; Duse, I. A.; Freeth, R.; Jager, N. W.; et al. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Life starts as a seed. When it rains, the seed begins to sprout and puts roots into the ground – and when the sun shines, the seed begins to grow. Southern Transylvania is full of precious seeds, which are growing at this very moment, to become a diverse landscape of flowers and trees. As these flowers and trees continue to grow and spread, they are turning into a beautiful garden. The seeds we write about in this book are the many activities, ideas and projects undertaken by people living and working in Southern Transylvania to create a better future for both people and the environment. This book is devoted to a vision for a sustainable and beautiful Transylvania, envisaged and pursued by a diverse range of people. In communicating this shared vision, we give a voice to local ideas and ideals, and show tangible ways to reach a future that can make Southern Transylvania a global role model for a sustainable region, in which people and ecosystems alike can thrive. Our target audience is broad, and includes the civil society sector in Transylvania, policy makers, and local community members; but also scientists working in other parts of the world who seek to work with communities in similar ways to what we present here. Throughout this book, we showcase positive examples of sustainability initiatives already underway in Southern Transylvania. In addition to short examples in the main text, several chapters contain boxes with detailed examples, some of which are contributed directly by local people. Of course, the examples we draw on are not an exhaustive list – we are acutely aware that there are countless positive examples in addition to the ones we present, some well-known, and some largely unknown to date. The examples we present thus should not be seen as “the best” examples of sustainability initiatives, but were chosen based on our knowledge, and in order to provide an overview of the range of different sustainability activities currently underway. This book has been a truly collaborative effort. It involved coordinating a large author team of researchers, as well as drawing on the input of many different stakeholders, who we acknowledge in the various boxes showcasing examples throughout the book. We greatly appreciate everyone’s constructive input! We hope this book will inspire, inform, and empower the people in Southern Transylvania and beyond to take charge of their region – for their own benefit, the benefit of their children, and the benefit of all other people and living beings we share our planet with.
Strategies for a Sustainable Southern Transylvania
Keywords: Sustainability; Southern Transylvania; Romania